THE USE OF GOOGLE TRANSLATE TO SUPPORT SPEAKING ACHIEVEMENT IN BASIC LEVEL OF Z-GENERATION INTERNATIONAL FOUNDATION - Afandi, Ahmad Rofat; Kurniawan, Erwin Hari; Amroni, Agus (FKIP UNISKA, 2023)
Speaking allows people to communicate with one another. Speaking skills are more difficult for new English students to learn than other English skills. A tutor uses Google Translate to support basic speaking in the Pre-speaking class. This motivates students and teachers to use the app to search for vocabulary as they express ideas. The results showed that using Google Translate to support speaking achievement in basic level of Z-Generation International Foundation students had a positive effect. This is a qualitative descriptive study. The researcher collected data through interviews, observations, and documentation on period 10th June 2022. This study shows that using Google Translate to support speaking skills increases students' interest in regularly practicing their speaking skills. For teachers, this method can produce positive results in teaching and learning. This can be seen in the fact that students are motivated and interested in speaking in class or outside of class on a regular basis.